(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Use of hydrogen as energy carrier, is one of the most promising alternatives in for near future. In order to achieve this, it has been worked on different routes that allow optimal processes of obtaining hydrogen with features that enable it to become a permanent power source. The different catalytic pathways for hydrogen production require improvement of various processes, such as design and synthesis of active and stable catalysts. In this regard and in order to understand the influence of the preparation method on properties and activity of the catalysts, in this work were prepared mixed oxides of Co-Mg-Al using two different methods: coprecipitation or conventional method (OMCo-cop) and ultrasound assisted co-precipitation (OMCo-US) , were prepared. The catalysts were characterized by XRD, surface area, temperature programmed reduction and catalytic activity was determined for the production of H2 by oxidative team reforming of of ethanol (OSRE by its acronym). The results indicate that the use of ultrasound decreased significantly the time catalyst synthesis, without affecting properties of the obtained solid. Ultrasound assistance caused an increase in surface area and the reducibility OMCo-US. Although both catalysts exhibit excellent catalytic performance, the OMCo-cop has greater yield to H2 and C1 compounds, while OMCo-US produces oxygenated compounds C2 and C3, due to the presence of basic sites of great strength which promote condensation reactions among reaction intermediates.